A New Approach to Global Studies from the Perspective of Small Nations - Date, Kiyonobu; Laniel, Jean-François (Taylor & Francis, 2024)
• A comprehensive introduction to small states, with a mixture of detailed examples (Quebec and Japan) and a broader range of case studies; • Addresses core questions of what a "state" is, what it is for and the role of small states in the international system; • Refocusses the study of small states away from the usual case studies, refocussing on the North American and East Asian contexts. ; With emphasis on East Asian and North American examples - notably Japan and Quebec - Date, Laniel and their contributors take a new approach to the understanding of small nations and their role in the international system. Small nations, by their very nature, raise significant questions about what a nation is. Some small nations are sovereign states with relatively small populations and limited territory, others are nations within larger sovereign states, with distinctive cultures, governance structures or other features that differentiate them from their "parent" state. By focussing on non-European nations in particular, the contributors to this volume challenge our conceptions of what a small nation is and how it operates within the international system. They focus in particular on the nation-within-a-nation-state of Quebec and on Japan, supplemented by further examples from East Asia. By interrogating what these examples have to show us about the typology and character of small nations, they offer a critique of superpower and draw out the potential of small nation studies. A valuable resource for students and scholars of international relations and theories of the nation and nation state.